Adverse life events and subclinical symptoms of depression associate to In Vivo brain type 1 endocannabinoid receptor availability in healthy adults - Parkkali, Lilja (My University, 2023)
Exposure to adverse life events can induce a significant amount of stress and affect the stress regulation system in our body. Excessive exposure to stress may result in dysfunction of the main system that controls stress responses, known as the hypothalamic–pituitary–adrenal (HPA) axis. The endocannabinoid system (ECS) regulates the functioning of the HPA through the endocannabinoid type 1 receptors (CB1R) in the brain. The aim of this study was to explore associations between adverse life events and CB1R availability in healthy adults (n=21). Additionally, the possible link of this association to subclinical depressive symptoms was examined. Measures of exposure to adverse life events and the presence of subclinical depressive symptoms were obtained from self-report questionnaires. To investigate CB1R availability, PET imaging data with a cannabinoid type 1 receptor radioligand [18F]FMPEP-d2 was analysed using a region of interest design. CB1R availability was indexed by distribution volumes of [18F]FMPEP-d2 in six brain regions involved in stress regulation: the amygdala, anterior and posterior cingulate cortex, hippocampus, insula and prefrontal cortex. Associations between adverse life events, subclinical depressive symptoms and CB1R availability were examined using repeated measures analysis of variance. Early adverse life experiences and CB1R availability were inversely associated. No association was observed between later life adverse experiences and CB1R availability. Subclinical depressive symptoms were found to be inversely associated with CB1R availability, both independently and when adverse life events were used as a covariate. These results suggest that both exposure to adverse life events in childhood, along with subclinical depressive symptoms, modify the functional balance of the ECS in adulthood. These results suggest a role of ECS functioning in regulation of stress processing and response.
Keywords: adverse life events, endocannabinoid receptor 1, [18F]FMPEP-d2, PET-imaging